The Utilization of Plant Diversity by Tengger Tribe around Bromo Tengger Semeru National Park, East Java, Indonesia. Issue 1 (May 2019) - Rohman, Fatchur; Rahyu Lestari, Sri; Hari Utomo, Dwiyono; Purwanto; Juma, Yusri; Nur Arifah, Siti; Annisa, Yuslinda
Abstract: Tengger tribe is one of the tribes in Indonesia that live around Bromo Tengger Semeru National Park (BTSNP) area. BTSNP area inhabited by the Tengger tribe people is an area in Indonesia with high biodiversity. The local wisdom of the Tengger tribe is in terms of the use of natural resources for various requirements of their lives. This study aimed to explore the utilization of multiple plants by the Tengger tribe in Ngadas and Ranupani villages around BTSNP. This research used surveys and group discussion (GDF) methods involving traditional leaders and some people of the Tengger tribe. The data obtained were analyzed descriptively and qualitatively. The results showed that the plants used for traditional medicinal materials were 25 species, food sources were 17 species, industrial materials and household were 11 species, building materials were 17 species, ecological functions were nine species, and traditional ritual ceremonies were seven species. The Tengger tribe used the natural resources in the form cultivation plants and non-cultivation plants to support in all aspects of their livelihood.